Preventing baby pig anemia, times of injection compared - D A Schoneweis; R K Bartel; J G Stuart; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
Fourteen litters (120 pigs) were used to study effects of iron injections on day one or day four after birth. No differences were detected in weight gains, hematological values of hemoglobin, packed cell volume, or red blood-cell count. The results indicate that injectable iron dextran may be administered on day one along with other husbandry practices (dipping navel cords, clipping needle teeth, ear notching) with no adverse effects. A disadvantage would be iron lost in pigs that die before day four from crushing, inanition, etc.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Baby pig anemia; Iron dextran